Mediation of Job Satisfaction in the Work Environment and Compensation of Employee Loyalty at PT Anugrah Tangkas Transportindo - Adelia Tien Novianti; Yuni Pambreni; Yupiter Yancik (International Publisher, 2024)
This research focuses on the mediation of job satisfaction on the relationship between work environment and compensation and employee loyalty at PT Anugrah Tangkas Transportindo Cengkareng Jakarta. The aim of this research is to evaluate the impact of the variables studied, such as work environment, compensation, job satisfaction and employee loyalty. The research approach is quantitative using a questionnaire as a data collection instrument. The research population consisted of 168 employees, and a sample of 65 employees was selected using non-probability sampling based on the purposive sampling method. Data analysis was carried out using the classic assumption test, t test, and path analysis (Sobel test) with the help of SPSS version 26 software. The research results show that there is a negative and significant relationship between the work environment and job satisfaction. Compensation has a positive and significant relationship with job satisfaction. The work environment positively and significantly influences employee loyalty, while compensation is negatively and significantly related to employee loyalty. Job satisfaction has a positive and significant impact on employee loyalty. Job satisfaction cannot mediate the influence of the work environment on employee loyalty. However, job satisfaction can mediate the influence of compensation on employee loyalty. In total, there are seven hypotheses tested in this research.